2020
DOI: 10.1002/ece3.6710
|View full text |Cite
|
Sign up to set email alerts
|

Miocene diversification of a golden‐thread nanmu tree species (Phoebe zhennan, Lauraceae) around the Sichuan Basin shaped by the East Asian monsoon

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Obligate outcrossing species is expected to have the values of Ho close to those of He as reported by Ye et al [31] for L. obtusiloba. For the genetic diversity of the dioecious tree species Phoebe zhennan (Lauraceae), Ho was higher than He (Ho = 0.243, He = 0.145), indicating low inbreeding [32]. Our results are similar to those of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Obligate outcrossing species is expected to have the values of Ho close to those of He as reported by Ye et al [31] for L. obtusiloba. For the genetic diversity of the dioecious tree species Phoebe zhennan (Lauraceae), Ho was higher than He (Ho = 0.243, He = 0.145), indicating low inbreeding [32]. Our results are similar to those of previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…The monsoon climate played a key role in the speciation and evolution of the species ( Sessa et al, 2012 ; Xiang et al, 2018 ; Liu et al, 2019 ). For example, the west lineage of Phoebe zhennan distributed around the Sichuan Basin was affected by the East Asian monsoon and further diversified at ∼7.12 Ma ( Xiao et al, 2020 ). The result of molecular dating indicated that the differentiation time of K. interior and its related species was consistent with the main uplifting event of QTP, and the intensifying of Asian interior aridification and monsoon climate.…”
Section: Discussionmentioning
confidence: 99%
“…In China, Phoebe wood is known for its excellent material for use in fine architecture, furniture, and carvings ( Li et al, 2017 ). Owing to habitat destruction and deforestation, the majority of surviving populations consist of fewer than 70 individuals ( Chen et al, 2020a ; Xiao et al, 2020 ). Over the years, cultivating, developing, utilizing, and conserving these valuable tree species have been difficult ( Gao et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%